UNPAID CARERS OF PERSONS WITH DISABILITIES IN AFRICA AND LATIN AMERICA: GENDER, HUMAN RIGHTS AND INVISIBILITY (African Disability Rights Yearbook, 2021)
Care is a complex issue that may be analysed using different perspectives and theories. It is also a biological imperative for human beings. For many people with disabilities, assistance and support are prerequisites to perform daily tasks and participate in society. In most cases, family is the primary provider of care and support and, within families; care is a role that falls disproportionally on women. The issue of unpaid carers (sometimes referred to as ‘caregivers’) may be analysed in terms of the gender equality impact that this role has as well as its social equality and human rights implications. Due to the fact that caring relationships involve carers as well as those they care for, public policies face the challenge of addressing the needs and claims of two groups which are different but related. In developed countries such as the United States, Spain and Australia, governments have developed policies to address this issue. In contrast, Africa and Latin America show that it is still an invisible concern. Family caregivers provide care in conditions of fragility and lack of resources that allow situations where the rights of persons with disabilities are violated and rights of their family are ignored.
Keywords: caregivers; gender equality; social equality; rights of persons with disabilities are violated